Electrical Properties of Tropical Fruit Extracts: Effects of EM4 Fermentation and Thermal Processing - Safitri, Wulan Dwi; Wardana, Dian; Ramadhan, Dwi Sapri; Fahmi, Jaman; Shallomita, Grace; Putri Ayunicha; Irma Syahputri; Siregar, Nuraini; Ahmad Nasir Pulungan; Moondra Zubir (Universitas Negeri Medan, 2025)
This study examines the electrical properties of fermented pineapple and lime extracts subjected to Effective Microorganism 4 (EM4) fermentation and thermal treatment at varying temperatures. The fermentation process was conducted over a period of six days, with temperature conditions set at 30°C and 70°C. The results indicate that the lime extract generated higher voltage and current outputs compared to the pineapple extract, particularly on the sixth day of fermentation. Furthermore, the thermal treatment revealed a more pronounced electrical response in lime extract, as evidenced by a greater increase in current at elevated temperatures. These findings suggest that lime extract, when combined with EM4 fermentation and optimal thermal conditions, exhibits greater potential for application in alternative bioelectric energy generation.